2021
DOI: 10.1108/sbr-09-2020-0113
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility in the wake of COVID-19: multiple cases of social responsibility as an organizational value

Abstract: Purpose Although corporate social responsibility is a well-researched concept, very few studies have studied organizational social responsibility in the face of internal/external crises. Therefore, this paper aims to examine various firms' organizational social responses to COVID-19 as an external crisis, particularly in terms of the way organizations use their resources to address social problems and the real intention behind these, and the changing organizational drivers influencing such behaviors. Design/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 49 publications
3
29
0
Order By: Relevance
“…However, this study subscribes to principles of the appropriateness of the data gathered suggested by O’Reilly and Parker (2013). In this study, the interview questions were developed by revisiting previous research that draws upon stakeholder theory both from an empirical and conceptual perspective on crisis situations (Ahmed et al , 2021; Alpaslan et al , 2009; Burga and Rezania, 2016; Hannah et al , 2021; McKnight and Linnenluecke, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this study subscribes to principles of the appropriateness of the data gathered suggested by O’Reilly and Parker (2013). In this study, the interview questions were developed by revisiting previous research that draws upon stakeholder theory both from an empirical and conceptual perspective on crisis situations (Ahmed et al , 2021; Alpaslan et al , 2009; Burga and Rezania, 2016; Hannah et al , 2021; McKnight and Linnenluecke, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…descriptive, normative thesis). Along these lines, Ahmed et al ’s (2021) study revealed that, in some situations, companies used their own resources to alleviate society’s needs during the initial stages of the crisis, for instance, by manufacturing high-in-demand sanitising products. Ahmed et al (2021) posit that swift and genuine responses to the crisis came from different companies involved in a variety of industries, all of which use their distinctive capabilities while offering their resources to support local communities and governments.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A majority of the studies focused on how CSR (broadly defined by multiple authors as companies' commitments to voluntary efforts to act ethically toward multiple stakeholders, or lack thereof) helped companies to navigate (or not) the challenges of the pandemic. A case study of seven organizations operating in different industries and countries showed that these firms used similar CSR activities to utilize their resources to achieve societal, and not just economic, goals, to help respond to the crisis (Ahmed et al, 2021 ). Mattera et al ( 2021 ) reported that long‐term CSR strategies and a strong commitment to sustainable development helped companies overcome periods of economic crisis.…”
Section: Introductionmentioning
confidence: 99%
“…spiritual, emotional and psychological) are crucial predictors of sustainability (Zhang et al , 2021). While the COVID-19 pandemic has challenged these human capacities by precipitating a global economic downturn, thereby affecting the continued existence of numerous organizations, which the human capital serves (Ahmed et al , 2021). Moreover, restrictions on the movement of people and commodities and transportation and logistics came into place concurrently with the growing demand for myriad goods and services (Millard, 2020).…”
Section: Introductionmentioning
confidence: 99%